Computational Fluid Dynamic Analysis Supports the Hemodynamic Stability of Hybrid Combinations With the AFX Bifurcate and Nitinol-Based Proximal Segments in Solutions of Failed Endovascular Aneurysm Repair. (November 2021) - Georgakarakos, Efstratios; Ioannidis, Georgios; Raptis, Anastasios; Xenos, Michalis
Hybrid endograft combinations of two or more different types of covered stents are rarely reported to treat complex abdominal aortic aneurysm cases or primary and secondary endoleaks. Clinical and laboratory data regarding the clinical efficacy and mechanical stability of such combinations are lacking. Based on a recently published case report, we describe and comment on the hemodynamic profile of a representative simulated hybrid case of AFX and Nitinol-based proximal cuff and support the stability of this combination in non-angulated cases.